Susceptibility Test of Aedes aegypti Larvae to Temefos (Abate) - Tuti Maula Fauziah; Firda Yanuar Pradani; Ary Nurmalasari (LPPM STIKes Muhammadiyah Ciamis, 2023)
Dengue fever is an infectious disease transmitted by the Aedes aegypti mosquito. Temefos is a tool used in controlling Aedes aegypti larvae and its use for a long time without based on rules can cause resistance. This study aims to determine the susceptibility status of Aedes aegypti larvae to Temefos in the Ciamis and Cimaragas areas. The method of this research is experimental with samples obtained from residential areas in Ciamis and Cimaragas sub-districts then hatched into instar IV larvae at the Parasitology Laboratory of STIKes Muhamamadiyah Ciamis in May 2019. The results of the test on temefos 0.1 g showed that Aedes aegypti larvae from both regions obtained the results of Ciamis (100%) and Cimaragas (100%) sub-districts were still susceptible to temefos. From these results it can be concluded that the test larvae from both areas are still susceptible to temefos so that the tool can still be used as a larvicide, especially in controlling Aedes aegypti mosquitoes.